Changing Our Mental and Emotional Trajectory (COMET): The Feasibility and Acceptability of a Rural Community-Based Strategy to Prevent Mental and Emotional Health Problems - Linda Zittleman; Maret Felzien; Kristen Curcija; Christopher Bennett; Kaitlyn Bennett; Joseph Carrica; Christin Sutter; Ashley Sherrill; John M Westfall (Journal of Primary Care & Community Health)
Introduction: People in rural regions frequently lack resources for mental health support. Changing Our Mental and Emotional Trajectory (COMET) is a universal, community-based program designed to address mental and emotional health issues early and prevent crises. COMET Community Training is a short, interactive training that teaches people how to initiate a supportive and potentially emotional conversation using the simple, 7-item COMET Conversational Gravity Assist. This article describes and reports on the feasibility and acceptability of COMET and its Community Training. Methods: COMET was developed using a participatory research approach by community members and health professionals living in a rural region and their research partners. COMET Community Trainings were conducted over a 22-month period. Surveys were administered to attendees before and after training to describe attendees’ characteristics, view on content, and impact on intention to use COMET components. Field notes were completed by trainers to document the date and number of attendees. Results: Over 700 people attended 60 Community Trainings. Questionnaires were completed by 644 trainees before and 580 after training. Of pre-survey respondents, 25% worked in education and 15% in farming/ranching. Post-survey respondents were 62% female, and 32% were between age 18 and 36. High levels of training satisfaction were reported. Average likelihood of using items in the COMET conversational guide increased significantly from pre to post training. On a scale of 1 to 10, nearly 80% of respondents rated their likelihood of using COMET in the next 3 months a 7 or higher. Conclusions: COMET Community Training is a feasible program that effectively reaches a range of community members and improves the likelihood that they will initiate conversations when concerned about someone else’s mental health. Results lay the groundwork for COMET as an intervention that promotes mental and emotional well-being to address inequality in mental health for people living in rural communities.